Pengaruh Dana Pihak Ketiga dan Total Aset Terhadap Return On Assets di BPRS Al Salaam Amal Salman Periode 2016-2020 - Prita Puji Setiati; Mimin Mintarsih Mintarsih; Bahmid I Magi (Ma'soem University, 2021)
Based on the results research, the background of this research is the fluctuations Return On Assets (ROA) which is influenced by internal factors, namely of Third Party Funds and Total Assets at BPRS Al Salaam Amal Salman. This study aims to determine how the effect of Third Party Funds and Total Assets on ROA at BPRS Al Salaam Amal Salman either partially or simultaneously. The object of research in this report is Third Party Funds, Total Assets to ROA at BPRS Al Salaam Amal Salman. The type of research is quantitative associative, the type of data is secondary data and uses data collection techniques in the form of documentation and literature study. The sampling technique is non-probability sampling, with a population of all quarterly financial reports of BPRS Al Salaam Amal Salman. While the type of sample used is purposive sampling, with a sample of quarterly financial statements of BPRS Al Salaam Amal Salman for the 2016-2020 period. The results showed that there was a significant but negative effect between Third Party Funds on ROA at BPRS Al Salaam Amal Salman with the results of the t-test where the value of tcount > ttable (-2,041 > 1,734), and there was a significant effect but in the negative direction between Total Assets on ROA at BPRS Al Salaam Amal Salman with t-test results where tcount > ttable (-2,034 > 1,734), while simultaneously there is no effect between Third Party Funds and Total Assets on ROA at BPRS Al Salaam Amal Salman with F test results where Fcount < Ftable (1,973 < 2,64).